Treatment with urea as an alternative to tolvaptan for the syndrome of inappropriate secretion of antidiuretic hormone - I. Gómez Valbuena; L. Alonso Pérez; D. Alioto; I. Cañamares Orbis; J. M. Ferrari Piquero (Elsevier, 2014)
The syndrome of inappropriate secretion of antidiuretic hormone (SIADH) is an affectation that causes hyponatremia among other symptoms. Currently the family of drugs of choice for this syndrome are vaptans, among them the tolvaptan, antagonists of vasopressin. Urea acts as an osmotic diuretic producing sodium retention. We report a case in which the change from the urea treatment with tolvaptan in SIADH allowed to keep the answer to a much lower cost. Female, 83 years old, was admitted to our hospital as he revealed severe hyponatremia (108 mEq / L) over a scan from a fall at home. Suspecting SIADH during admission was prescribed on three types of treatments: Water restriction and saline for 7 days followed by 15 mg tolvaptan and finally was prescribed 15 grams of urea every 12 hours. Serum sodium levels of patients during the first treatment did not increase enough, so it was changed to tolvaptan, during which serum sodium levels rose to normal ranges. Considering that the treatment would be long-term was changed to urea, during it, the levels of serum sodium had a slight increase. The patient was discharged with the pattern of urea indefinitely.The daily cost of treatment with tolvaptan is 66,91 €, as opposed to 0,30 € of urea. In cases such as these, urea prepared like pharmacy compound, is an alternative to tolvaptán in SIADH to a markedly lower cost.